2017
DOI: 10.2217/fmb-2017-0054
|View full text |Cite
|
Sign up to set email alerts
|

Biological Evaluation of Novel Curcumin–Pyrazole–Mannich Derivative Active Against Drug-Resistant Mycobacterium Tuberculosis

Abstract: Taken together, CPMD-6d dihydrochloride exhibits all properties to be positioned as a novel molecule of interest for treatment of tuberculosis. Graphical abstract: [Formula: see text].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Moreover, curcumin and the isoxazole analogs, fashioned untimely reductions in the amounts of relevant gene transcripts which were diverse. [43] Among them, compounds 17 and 18 demonstrated potent cytotoxic activity against HNSCC cell lines. [59] Isoxazole and pyrazole derivatives were less prone to nucleophilic benzyl mercaptan addition than curcumin.…”
Section: Curcumin Pyrazole and Isoxazole Analogs As Anticancer Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, curcumin and the isoxazole analogs, fashioned untimely reductions in the amounts of relevant gene transcripts which were diverse. [43] Among them, compounds 17 and 18 demonstrated potent cytotoxic activity against HNSCC cell lines. [59] Isoxazole and pyrazole derivatives were less prone to nucleophilic benzyl mercaptan addition than curcumin.…”
Section: Curcumin Pyrazole and Isoxazole Analogs As Anticancer Agentsmentioning
confidence: 99%
“…Molecular docking studies discovered the promising binding type of pyrazole compound 2 in the SH2 domain of STAT3 (curcumin pyrazole and curcumin click chemistry analogs 6 and 16-18). [43] Among them, compounds 17 and 18 demonstrated potent cytotoxic activity against HNSCC cell lines. Amusingly, derivatives 16 and 17 have important effect on pSTAT3 phosphorylation.…”
Section: Curcumin Pyrazole and Isoxazole Analogs As Anticancer Agentsmentioning
confidence: 99%
“…Three-week treatment with 25 mg/kg of CPMD-6-dihydrochloride showed a significant reduction in the bacterial load in the lung of infected six-week-old BALB/c mice by 1.06 log10 in comparison to 100 mg/kg of EMB treated group. CPMD-6-dihydrochloride also reduced bacterial counts by 0.63 log10 while EMB reduced by 0.51 log10 in the spleen, demonstrating that CPMD-6 dihydrochloride has superior efficacy with respect to a reduction in mycobacterial CFU at one-fourth of the dosage in comparison to EMB in the murine MTB infection model [ 45 ].…”
Section: Antimycobacterial Activity Of Curcumin Synthetic Derivativesmentioning
confidence: 99%
“…Multiple studies made earlier reveal that the MTB growth inhibiting potential of curcumin is satisfactory but not that excellent. To overcome this disadvantage, Singh et al 116 synthesized 21 curcumin derivatives and evaluated them for their in vitro and in vivo antimycobacterial activity. They reported that a derivative named CPMD-6d dihydrochloride exhibited bactericidal activity against MTB in a concentrationdependent manner (MIC = 2 μg/ml), even against drugresistant strains.…”
Section: Curcumin and Its Important Nanoformulations Against Mtb Infe...mentioning
confidence: 99%